Changes in Gene Expression in the Rat Hippocampus Following Exposure to 56Fe Particles and Protection by Berry Diets - Shukitt-Hale, Barbara; C. Lau, Francis; Cheng, Vivian; Luskin, Katharine; N. Carey, Amanda; Carrihill-Knoll, Kirsty; M. Rabin, Bernard; A. Joseph, James (Central Nervous System Agents in Medicinal Chemistry, 2013)
Exposing young rats to particles of high energy and charge, such as 56Fe, enhances indices of oxidative stress and inflammation and disrupts behavior, including spatial learning and memory. In the present study, we examined whether gene expression in the hippocampus, an area of the brain important in memory, is affected by exposure to 1.5 Gy or 2.5 Gy of 1 GeV/n high-energy 56Fe particles 36 hours after irradiation. We also determined if 8 weeks of pre-feeding with 2% blueberry or 2% strawberry antioxidant diets could ameliorate irradiation-induced changes in gene expression. Alterations in gene expression profile were analyzed by pathway-focused microarrays for inflammatory cytokines and genes involved in nuclear factor-kappa B (NF-κB) signal transduction pathways. We found that genes that are directly or indirectly involved in the regulation of growth and differentiation of neurons were changed following irradiation. Genes that regulate apoptosis were up-regulated whereas genes that modulate cellular proliferation were down-regulated. The brains of animals supplemented with berry diets demonstrated an up-regulation of some protective stress signal genes. Therefore, these data suggest that 56Fe particle irradiation causes changes in gene expression in rats that are ameliorated by berry fruit diets.
Keywords: nuclear factor-kappa B